Pengaruh Ketebalan Elektroda Kerja TiO2 Transparan terhadap Kinerja Dye Sensitized Solar Cell (DSSC) sebagai Aplikasi Solar Window - Nadya Aruma Dewi; Fahru Nurosyid; Agus Supriyanto; Risa Suryana (INDONESIAN JOURNAL OF APPLIED PHYSICS, 2017)
Senditized Dye Solar Cells (DSSC) consist of photoelectrode, dye, electrolyte and counter electrode which is one of the photochemical electric cells. In this article will discuss the influence of the thickness of the electrode on the electrical properties. Electrodes made by screen printing method. Screen by type T-49. TiO2 deposited on the FTO variation of the number of layers to obtain a thickness of 1, 2, 3 and 4. DSSC tested thickness by Screen Electron Microscopy (SEM), absorbance test by UV Visible Lambda 25 and characterization of current and voltage test by Keithley Measurenment 2602A. The test results showed the thickness of the TiO2 electrode thickness (1.5 ± 0.2) μm, (2.9 ± 0.5) μm, (3.5 ± 0.6) μm, and (4.5 ± 0.8 ) μm. Based on the test results absorbance maximum value contained in thickness (4.5 ± 0.8) μm having a dye adsorbed at most and have the highest efficiency  2.41%.